Sustainable Amylopectin‐Derived Miniwindmills for Moisture‐Induced Electric Generation. Issue 11 (6th November 2022) - Sun, Bianjing; Xu, Dan; Wang, Zengbin; Pang, Bo; Wang, Jiaxiu; Sun, Dongping; Zhang, Kai
Abstract : Energy Harvesting Membranes In article number 2200084 Kai Zhang, Dongping Sun and co‐workers present a sustainable and feasible approach to fabricate flexible and robust amylopectin‐derived membranes for moisture‐induced energy harvesting directly from the ambient environment. As‐designed energy‐harvesting powerful mini‐windmill generators can deliver a sustained output performance under the stimuli of humidity.